The reflection of modern trends of linguistics in Uzbek poetry (Zien Journal of Social Sciences and Humanities, 2022)
This article describes the pragmalingvistic foundations of modern linguistics using anthropocentric trends, how modern approaches to linguistics are reflected in Uzbek poetry